(untitled) (World Bulletin of Social Sciences, 2024)
This article talks about the sanctity of the family, the traditions typical of Uzbek families. In the matters of education and morals, the rich historical, cultural and educational heritage, traditions and values of our people, and the family relations necessary for growing up to become a fully mature and perfect person, relying on the teachings of our great thinkers. attention is paid to the most important issues, the duty of parents in the family and their responsible approach in this regard